Efeito de resíduos vegetais de milheto (Pennisetum americanum) e da calagem em algumas propriedades físicas e químicas de um nitossolo vermelho em sistema de semeadura direta - Coneglian, Cristiano; Moraes, Maria Helena [UNESP] (My University, 2006)
This work studied alterations of physical properties of a distroferric red nitosol due to millet (Pennisetum americanum) covering, with or without liming, in a no-tillage system during the agricultural years of 1999/2000 and 2000/2001, using soybean and corn as culture succession. 6m×10m plots, with and without millet as vegetal covering, received only one initial superficial application of limestone, 3.1 t ha-1 in the first half of each plot in order to obtain 70% base saturation (V), after the desiccation of the millet. Some physical properties as soil density, aggregate stability, > 2 mm aggregate proportion, macro and micro porosity were analyzed whereas the chemical analysis determined Ca and Mg macro nutrients, organic matter, soil pH and H+Al. Millet vegetal residues and surface liming did not alter soil density nor the average weight diameter (AWD), > 2 mm aggregate, soil macro porosity and organic matter content, twenty-four months after the no-tillage system implantation for studied experimental conditions. Soil micro porosity was significantly affected in layers deeper than 0.20 m, in treatment with millet and limestone. Calcium, magnesium and H + Al contents and the soil pH values suffered significant alterations in superficial layer, between 0-0.05 m.
Effect of millet residues (Pennisetum americanum) and liming on some physical properties of distroferric red nitosol in no-tillage system
Keywords: Aggregate stability; Calcium; Millet; No-tillage system; Porosity; Soil density; Crops; Density (specific gravity); Lime; Organic minerals; pH; Soils; Vegetation; aggregate stability; liming; maize; millet; Nitosol; porosity; soil fertility; soil nutrient; soil organic matter; soil property; soybean; zero tillage; Glycine max; Pennisetum glaucum; Zea mays